2019
DOI: 10.1109/led.2019.2896939
|View full text |Cite
|
Sign up to set email alerts
|

Physical Origin of the Gate Current Surge During Short-Circuit Operation of SiC MOSFET

Abstract: During short-circuit of a vertical 4H-SiC power MOSFET, a high gate current starts to flow through the gate dielectric. We demonstrate that the Schottky emission is the main physical mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…4. As introduced in section I, it is expected that FN tunnel injection will be the governor mechanism [4,3] because of the oxide thickness and temperature range of this experiment.…”
Section: Methodology and Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…4. As introduced in section I, it is expected that FN tunnel injection will be the governor mechanism [4,3] because of the oxide thickness and temperature range of this experiment.…”
Section: Methodology and Resultsmentioning
confidence: 97%
“…This is evidenced by Chen et al [29], who observed an increase in the gate-source current before failure happened during a shortcircuit test and relate this with tunneling current. However, a recent study [3] suggests that Schottky emission may be the predominant phenomenon in this gate current increase.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Such a stress dynamic can reveal specific drift mechanisms or even degradation mechanisms of weak region which are not visible in nominal operation [2]. For example, the strong gate-source leakage-current is caused by a hot electron injection through the thin gate oxide [4] and the high drain-source peak current decreases as the channel mobility decreases at high temperature [12]. As a matter of fact, in order to model and fit the thermal-dependant physical mechanisms involved during the short circuit operation, an extended electrothermal modelling is needed.…”
Section: Circuit-type Electro-thermal Modellingmentioning
confidence: 99%
“…The very thin gate-oxide (typically 50nm against 100nm for silicone-planar device) under a high gate field (4MV/cm compared to 10MV/cm breakdown field of the SiO2) is highly stressed in short-circuit operation. Indeed, the junction temperature can reach at least 1300K, leading to hot carrier injection in the oxide that could explain the possible weakness of the gate region and its variability in extreme operation [3], [4].…”
Section: Introduction and Objectivesmentioning
confidence: 99%